A regional-scale geochemical survey of soil O and C horizon samples in Nord-Trøndelag, Central Norway: Geology and mineral potential. (October 2015) - Reimann, C.; Schilling, J.; Roberts, D.; Fabian, K.
Highlights: Soil O and C horizon samples from Nord-Trøndelag are used to investigate the exploration potential. All major mineral deposits are marked by single or multi-element anomalies in at least one of the soil horizons . Maps of several elements and the Pb isotopes clearly reflect important geological features in Nord-Trøndelag. New anomalies highlight the mineral potential of the area. Abstract: A highly efficient, low-density sampling strategy was employed to study the geochemical expression of geological bodies and the mineral potential on the county scale in Central Norway. Soil O and C horizon samples ( N = 752) were collected in Nord-Trøndelag and parts of Sør-Trøndelag, and analysed for 53 chemical elements (Ag, Al, As, Au, B, Ba, Be, Bi, Ca, Cd, Ce, Co, Cr, Cs, Cu, Fe, Ga, Ge, Hf, Hg, In, K, La, Li, Mg, Mn, Mo, Na, Nb, Ni, P, Pb, Pd, Pt, Rb, Re, S, Sb, Sc, Se, Sn, Sr, Ta, Te, Th, Ti, Tl, U, V, W, Y, Zn, and Zr) and Pb isotopes in an aqua regia extraction. At the sample density of one site/36 km 2 the four metal deposits, which have been mined in the area within the last 50 years were all detected as geochemical anomalies. In addition, a number of new anomalies that may warrant follow-up surveys were found. In terms of geology the Grong–Olden Culmination is marked by a distinct 206 Pb/ 207 Pb isotope anomaly. Geochemical differences distinguish the most important belts of mafic metavolcanic lithologies in the area. Though the Fosdalen iron ore deposit is only marked in the soil O horizon, the C horizon outlines the more prominent anomalies of possibly economic interest. Climatic factors like the input of marine aerosols along the coast are clearly visible in the soil O horizon. Low-density geochemical mapping of two sample materials provides important complementing information for the interpretation of the geochemical variation in Nord-Trøndelag county.